ANTHRAQUINONE DYESTUFF AND GROWTH OF GALIUM ODORATUM ((L.) SCOP.) RHIZOMES IN RELATION TO ECOPHYSIOLOGICAL AND ONTOGENIC CONDITIONS - Olfa Boussadia; Bertrand Martin; Aurore Nicolas; Monique Bodson (European Scientific Journal, ESJ, 2015)
Galium odoratum, a member of the Rubiaceae family is known to accumulate anthraquinone dyestuff in the rhizome. The objective of our research was to document ecophysiological variables that modulate the anthraquinone dyestuff content and the growth rate of the underground part of this species. Several variables were taken into consideration : (1) the plant population phenology and the geographic origin of the plant population, for plant material collected in 4 natural stands identified in forests of Belgium, Grand-Duchy of Luxembourg and France, (2) the plant growth conditions, i.e. natural stands vs controlled environment and (3) the plant propagation path, i.e. clonal vs seed propagation. In natural stands, the anthraquinone dyestuff content varied with the plant phenology, being minimal at full flowering stage and the highest at leaf yellowing. It also varied depending on the geographic location of the plant population. Such a difference between plant populations was not observed when plants were grown in controlled environment. Typically, the anthraquinone dyestuff of the plant rhizome was higher in controlled environment than in natural stands, suggesting a strong impact of the growth conditions on anthraquinone biosynthesis. Additionnally, the plant propagation path does not influence the anthraquinone dyestuff content, but when newly formed rhizome was separated into fragments of increasing age –from 27 to 105 days-, a linear increase of the dyestuff with the rhizome ageing was observed.